Status of internet of things in the University of the Philippines Diliman Main Library - Enriquez, Neil Mark O.; Pascua, Sonia M. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2016)
The study aimed to address the Status of Internet of Things in the University of the Philippines Diliman Main Library, by assessing the status, technology integration and student knowledge on IOT. It was necessary to address the problem due to the promising effects of disruptive technologies.
A User-Centered Design was used in the methodology which allows students to be part of the process (Manzari, 2013). The process revolves around the concept that the end-user should be part of the planning, development and assessment of feedback in a program, this is not only limited to software but also to business processes. The study uses a descriptive approach to know the status and answers the environment of the libraries in relation to Internet of Things. It answers the questions of technology implementation of libraries.
The preliminary studies allowed to gauge the perception and familiarity of the students on Internet, it was then used to help create the statement of the problems, in line with this i.e. these interviews with a library official in UP Diliman, uncovered the current implementation of technology and IOT in the library. The prevalence of RFID allowed the library to use it as a stepping stone in automation and the use of digital methods. However implementation has just been practiced in the first quarter of 2016 due to problems experienced in 2015 in the Filipiniana Section of the Main Library, it has not yet been adopted by the other sections. Students on the other hand have shown little familiarity with Internet of Things and expressed a need for programs that allow and enhance general knowledge, training and demonstration of concepts related to IOT. This puts education and seminars to inform students and and expose them to IOT.
The statistical analysis of Fleiss' Kappa Interrater Reliability shows that when large amount of respondents that data allows for a lower reliability due to the difference of weighted means in scores. However when Kruskal-Wallis One Way Analysis of Variance was used, the test allows for the comparison between different sets of responses grouped in colleges making the data easier to analyze its reliability.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines (Diliman) Main Library; Computer networks -- Management; Library information networks